2022
DOI: 10.1155/2022/7265769
|View full text |Cite
|
Sign up to set email alerts
|

A Network Meta-Analysis of the Clinical Efficacy and Safety of Commonly Used Chinese Patent Medicines in the Auxiliary Treatment of Poststroke Depression

Abstract: Background. Poststroke depression (PSD) is a serious complication of clinical cerebrovascular disease. Patients not only have depression-related emotional symptoms but also have physical symptoms, such as autonomic dysfunction. At the same time, patients with varying degrees of depression will delay the neurological function of stroke patients. The recovery time of cognitive function and limb function will increase the risk of accidental death and even aggravate the mortality of cerebrovascular disease. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…No patient withdrew from the study because of adverse reactions, and the results showed that Wuling capsule has a good safety profile. A systematic study on patients using Wuling capsules in reallife situation using the centralized monitoring method in hospitals, also showed that the incidence of adverse reactions to Wuling capsules was rare [17]. Chinese traditional patent medicine treatment reduces patients' stigma and improves patients' compliance.…”
Section: Discussionmentioning
confidence: 99%
“…No patient withdrew from the study because of adverse reactions, and the results showed that Wuling capsule has a good safety profile. A systematic study on patients using Wuling capsules in reallife situation using the centralized monitoring method in hospitals, also showed that the incidence of adverse reactions to Wuling capsules was rare [17]. Chinese traditional patent medicine treatment reduces patients' stigma and improves patients' compliance.…”
Section: Discussionmentioning
confidence: 99%
“…When CSS was used as the primary treatment, a network meta-analysis of seven traditional Chinese medicines as adjunctive therapy for post-stroke depression revealed that CSS has unique advantages in enhancing clinical efficacy compared to some other traditional Chinese medicines ( Yu et al, 2022 ). In a clinical randomized controlled trial involving 86 patients, CSS demonstrated a significantly higher clinical effectiveness rate compared to the control group (97.67% vs. 81.40%) and substantially alleviated depression levels of patients ( Zhang, 2016 ).…”
Section: Clinical Studies On Chaihu-shugan-sanmentioning
confidence: 99%